2013
DOI: 10.1007/s11104-013-1877-8
|View full text |Cite
|
Sign up to set email alerts
|

Potassium release characteristics, potassium balance, and fingermillet (Eleusine coracana G.) yield sustainability in a 27- year long experiment on an Alfisol in the semi-arid tropical India

Abstract: Aims In Alfisols, potassium (K) deficiency limits productivity, as these soils are poor in K-bearing minerals such as mica. As nutrient management practices greatly influence K nutrition of crops especially in the longer term, we evaluated the effects of 27 (1978-2004) years of cropping fingermillet (Eleusine coracana G.) under different manure and mineral fertilizer treatments on K release, balance and yield sustainability on K deficient Alfisols in the semi-arid tropical region of southern India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…Sometimes, negative apparent K balance might correspond to an increase in NH 4 OAc-K, as observed in a longterm experiment (27 years) conducted on a K-deficient Alfisol from southern India under finger-millet mono-cropping (Srinivasarao et al 2014). Irrespective of treatments, which were control (no amendments), FYM, FYM + 50% NPK, FYM + 100% NPK and 100% NPK (no organic source), K removal by crop was more than that added through FYM or fertilizer or their combination.…”
Section: Inceptisolsmentioning
confidence: 92%
See 2 more Smart Citations
“…Sometimes, negative apparent K balance might correspond to an increase in NH 4 OAc-K, as observed in a longterm experiment (27 years) conducted on a K-deficient Alfisol from southern India under finger-millet mono-cropping (Srinivasarao et al 2014). Irrespective of treatments, which were control (no amendments), FYM, FYM + 50% NPK, FYM + 100% NPK and 100% NPK (no organic source), K removal by crop was more than that added through FYM or fertilizer or their combination.…”
Section: Inceptisolsmentioning
confidence: 92%
“…Despite, NH 4 OAc-K increased by ~ 18% and ~ 39% (over initial content of ~ 59 mg kg −1 ) under FYM + 50% NPK and FYM + 100% NPK, respectively after 27 years of cropping. Over that supplied through external inputs and the exchangeable K, non-exchangeable K pool met the crop K demand (Srinivasarao et al 2014). Li et al (2017a) reported a decline in NH 4 OAc-K after 25 years of wheat-maize cropping with heavy inputs of N and P fertilizers in an alluvial soil of China.…”
Section: Inceptisolsmentioning
confidence: 98%
See 1 more Smart Citation
“…Uji korelasi menunjukkan parameter yang signifikan berkorelasi positif dengan IKT adalah C-organik (r = 0,728; P-value = 0,007; n = 12), N-total (r = 0,642; P-value = 0,024; n = 12) dan K-tersedia (r = 0,874; P-value = 0,000; n = 12). Nitrogen dan Kalium merupakan unsur makro esensial, dibutuhkan tanaman dalam jumlah yang cukup besar, sehingga ketersediaannya sangat penting dan perlu diperhatikan (Qiu et al, 2014;Srinivasarao et al, 2014). C-organik berhubungan dengan kualitas sifat fisik, kimia dan biologi tanah.…”
Section: Hasil Dan Pembahasanunclassified
“…Negative K balances subsequent to several crop cycles have been reported globally. Depletion of K stocks in soil resources has been reported due to suboptimal application rates of K fertilizers and manures in India (Srinivasarao et al, 2013(Srinivasarao et al, , 2014 and lack of fertilizer application in Africa (Hanao and Baanante, 1999). Changes in land use systems can also affect the status and form of K (Rezapour and Samadi, 2014).…”
Section: Introductionmentioning
confidence: 99%